A COMPREHENSIVE REVIEW OF CHRONIC MUSCULOSKELETAL PAIN IN THE ELDERLY - Thành Toàn, Võ (Journal of Health and Aging, 2025)
Musculoskeletal pain is highly prevalent among older adults, affecting 40–60% of this population and contributing significantly to disability and reduced quality of life. Chronic pain in the elderly is multifactorial and often underdiagnosed or undertreated due to complex clinical presentations, cognitive impairment, and misconceptions about pain as a normal part of aging. It is closely associated with geriatric syndromes such as falls, frailty, sleep disturbances, depression, and cognitive decline, and should be assessed in a comprehensive biopsychosocial context. Multimorbidity and polypharmacy further complicate treatment decisions. Non-pharmacologic strategies such as physical therapy, behavioral interventions, and mind-body therapies are strongly recommended. When medications are used, individualized dosing and careful monitoring are essential due to altered pharmacokinetics in older adults. Improving access to evidence-based non-drug therapies and strengthening clinical research are key strategies for enhancing pain care in this vulnerable population.
Keywords: chronic pain; older adult; musculoskeletal system; non-pharmacologic treatment; multimodal approach